The miR-1206 microRNA variant is associated with methotrexate-induced oral mucositis in pediatric acute lymphoblastic leukemia. Issue 8 (August 2017) - Gutierrez-Camino, Angela; Oosterom, Natanja; den Hoed, Marissa A.H.; Lopez-Lopez, Elixabet; Martin-Guerrero, Idoia; Pluijm, Saskia M.F.; Pieters, Rob; de Jonge, Robert; Tissing, Wim J.E.; Heil, Sandra G.; García-Orad, Africa; van den Heuvel-Eibrink, Marry M.
Abstract : Five-year survival rates of pediatric acute lymphoblastic leukemia (ALL) have reached 90% in the developed countries. However, toxicity because of methotrexate (MTX) occurs frequently. Variety in the occurrence of toxicity is partly determined by single nucleotide polymorphisms (SNPs) in coding regions. Recently, five SNPs in non-coding pre-microRNAs and microRNA processing (miRNA) genes were identified in association with MTX-induced oral mucositis. This study aimed to replicate the association of these miRNA variants in relation to MTX-induced oral mucositis in a prospective childhood ALL cohort. Three out of five SNPs with a minor allele frequency more than 0.15 [CCR4-NOT transcription complex ( CNOT4 ) rs3812265, miR-1206 rs2114358, miR-2053 rs10505168] were analyzed in 117 pediatric ALL patients treated with 5 g/m 2 MTX (DCOG ALL-10). Oral mucositis was defined as grade more than or equal to 3 according to the National Cancer Institute criteria. rs2114358 in miR-1206 was associated with oral mucositis [odds ratio (OR): 3.6; 95% confidence interval (CI): 1.1–11.5], whereas we did not confirm the association of CNOT4 rs3812265 (OR: 0.69; 95% CI: 0.27–1.80) and miR- 2053 rs10505168 (OR: 2.50; 95% CI: 0.76–8.24). Our results replicate the association between rs2114358 in miR-1206 and MTX-induced oral mucositis in childhood ALL. Genetic variation in miR-1206 has potential as a novel biomarker to predict MTX-induced toxicity. Abstract : Supplemental Digital Content is available in the text.